2010
DOI: 10.1186/1471-2202-11-31
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of bis(7)-tacrine against glutamate-induced retinal ganglion cells damage

Abstract: BackgroundGlutamate-mediated excitotoxicity, primarily through N-methyl-D-aspartate (NMDA) receptors, may be an important cause of retinal ganglion cells (RGCs) death in glaucoma and several other retinal diseases. Bis(7)-tacrine is a noncompetitive NMDA receptors antagonist that can prevent glutamate-induced hippocampal neurons damage. We tested the effects of bis(7)-tacrine against glutamate-induced rat RGCs damage in vitro and in vivo.ResultsIn cultured neonatal rats RGCs, the MTT assay showed that glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 47 publications
(70 reference statements)
2
41
0
1
Order By: Relevance
“…It is a powerful antioxidant exhibiting multifunctional properties, including anti-inflammatory, anti-apoptosis, neuroprotective effect (Sutherland et al 2006;Zhang et al 2007Zhang et al , 2008Peng et al 2008;Xie et al 2010). Recent researches showed that EGCG also reduced the glutamate excitotoxicity, promoted the viability of neuronal cells by inhibiting ionotropic Ca 2+ influx, reduced the excitotoxin-induced malondialdehyde (MDA) production and decreased the reactive oxygen species level in a dose-dependent manner (Lee et al 2004a,b;Fu & Koo 2006;Fang et al 2010;Yu et al 2010). Besides of that, EGCG was found to regulate the glutamate level by an increase in the glutamate uptake of astrocytes, and the activity of excitatory amino acid transporter 2 (EAAT2), the essential protein for the clearance of synaptically released glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…It is a powerful antioxidant exhibiting multifunctional properties, including anti-inflammatory, anti-apoptosis, neuroprotective effect (Sutherland et al 2006;Zhang et al 2007Zhang et al , 2008Peng et al 2008;Xie et al 2010). Recent researches showed that EGCG also reduced the glutamate excitotoxicity, promoted the viability of neuronal cells by inhibiting ionotropic Ca 2+ influx, reduced the excitotoxin-induced malondialdehyde (MDA) production and decreased the reactive oxygen species level in a dose-dependent manner (Lee et al 2004a,b;Fu & Koo 2006;Fang et al 2010;Yu et al 2010). Besides of that, EGCG was found to regulate the glutamate level by an increase in the glutamate uptake of astrocytes, and the activity of excitatory amino acid transporter 2 (EAAT2), the essential protein for the clearance of synaptically released glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…• The percentage of normal, early apoptotic, late apoptotic, and necrotic cells were calculated using FACS Calibur and Cell Quest software (Becton-Dickinson, Franklin Lakes, NJ, USA) [15] . …”
Section: Rna Interferencementioning
confidence: 99%
“…Holcombe et al reported that IOP threshold of ~70 mmHg for the maintenance of retinal perfusion and IOPs elevated ≤70 mmHg was consistent with the maintenance of GLAST activity in rat glaucomatous model in vivo (30), which was consistent with our result (40 mmHg pressure). Woldemussie et al found that the expression of GLAST increased and remained high for 2 months, following the elevation of IOP (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in rat glaucomatous models in vivo, however, the expression of GS showed little change for the first 3 weeks (13). Nonetheless, Zhang et al reported that the induced expression of GS was observed as early as 24 h following the IOP in elevation in the rat models of acute intraocular hypertension (31).…”
Section: Discussionmentioning
confidence: 99%